2010
DOI: 10.1177/0148607109357627
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Markers in Patients After Heart Surgery

Abstract: The standard dietary regimen followed during cardiological rehabilitation after major cardiovascular surgery aids recovery from surgical insult, but fails to normalize high glucose levels. Vitamin B12 supplementation should be encouraged because of its substantial reduction during the rehabilitation period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…429 Other studies of CABG patients have documented decreases in B complex vitamins such as B 6 , B 12 , and thiamine, which are essential for mitochondrial function. 416,427,430 Vitamin D levels have been shown to be important predictors of outcome after cardiac surgery. In a study of 4418 patients recovering from cardiac surgery, Zittermann et al 431 noted that 38.0% had deficient 25(OH)D values (<30 nmol/L).…”
Section: Vitamins and Supplementsmentioning
confidence: 99%
“…429 Other studies of CABG patients have documented decreases in B complex vitamins such as B 6 , B 12 , and thiamine, which are essential for mitochondrial function. 416,427,430 Vitamin D levels have been shown to be important predictors of outcome after cardiac surgery. In a study of 4418 patients recovering from cardiac surgery, Zittermann et al 431 noted that 38.0% had deficient 25(OH)D values (<30 nmol/L).…”
Section: Vitamins and Supplementsmentioning
confidence: 99%
“…In this study, 7 vitamin B 12 levels fell during the observation period, and the authors concluded that supplementation might be beneficial. The physiology of vitamin B 12 binding is pertinent to these findings.…”
Section: Vitamin B12mentioning
confidence: 55%
“…Table 2 presents the drugs patients received during the rehabilitation period in the Milan study 7 . A few of them are metabolized by the CYP3A4 system, but generally cardiologists avoid statins that share CYP3A4 inhibitors.…”
Section: Polypharmacy and Its Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with increased nutritional risk in our study were older, of lesser body weight and had higher extent or number of cardiovascular risk factors, especially diabetes, dyslipidemia, coronary artery disease and were cigarette abusers some time during their lifetime [29] . Also, those patients exhibited laboratory parameters change in terms of normocytic anemia, with reactive leukocytosis and thrombocytosis [30] .…”
Section: Discussionmentioning
confidence: 98%